Development Of Smart Working Assistance Application For J&T Express Couriers In Juwiring Klaten Branch - Umar Chamdani Nur; Muqorobin Muqorobin (Institut Teknologi Bisnis AAS Indonesia, 2020)
Technology applications have now been implemented in various fields, one of which is the application of goods delivery. This study aims to make it easier for couriers to classify packages based on the most optimal and most efficient addresses. The author interviewed a courier who works at J&T Express. The author concludes that the courier is still very difficult in determining which order of packages should be delivered first, because many couriers still do not know their own territory, let alone the areas of other colleagues that have to be backed up when one of their colleagues does not work. In this study the authors compile an application that can provide solutions to assist and facilitate couriers in grouping packages by address, by utilizing several application technologies that will be used in the development of this application. In addition to sorting packages based on address, this application can display the routes of addresses to be delivered so that couriers can be more familiar with the location to be directed so that it is easier to deliver goods. The results in this study indicate that in trials with couriers it gets a very good response, but in this application there are still some shortcomings. Thus, the development of this application is very suitable for use by couriers.